Operation Strategy Implementation for Business Plan at Material Handling Rental Services Startup LogisMe - Sidik, Satrio Riyono; Indradewa, Rhian; Hamdi, Edi; Sunaryanto, Ketut (Jurnal Ilmiah Universitas Batanghari Jambi, 2025)
Logistics and warehousing companies are often faced with a dilemma due to the high cost of procuring heavy equipment. Although demand for logistics services continues to increase, especially after the Covid-19 pandemic, many companies are struggling to meet their equipment needs. This document outlines the operational strategy plan for LogisMe, a Material Handling Rental Services startup company. The plan leverages a virtual office model for increased efficiency and utilizes a staged workshop rollout across Indonesia to serve customer needs. LogisMe offers rental units and an integrated monitoring portal platform (SaaS) with customizable modules for enhanced customer experience. The key focus is achieving a 90% Service Level Agreement (SLA) through efficient operations and effective quality management practices aligned with ISO standards. The ultimate goal is to become a market leader in innovative, environmentally friendly, reliable, and high-tech rental solutions for material handling, cleaning equipment, and logistics systems.